Evidence-Based Integrated Waste Management Framework For Adiwiyata Schools: A Systematic Review and Bibliometric Mapping - Asiah Asiah; Ahmad Nubli Gadeng; Ichwana Ichwana (Borneo Research and Education Center, 2026)
Waste management has become an increasingly significant global challenge, requiring sustainable approaches such as waste-to-energy (WtE), which can reduce waste volume while generating alternative energy. However, existing waste management studies are still dominated by technical perspectives and have not sufficiently integrated educational dimensions within school environments. This study aims to analyze the development of literature related to school-based waste management using a waste-to-energy approach and to develop an integrated waste management model for Adiwiyata schools. The study employed a systematic literature review (SLR) based on PRISMA 2020 guidelines combined with bibliometric analysis using VOSviewer. Data were collected from Scopus publications from 2006–2025, resulting in 133 articles selected for analysis. The findings indicate a significant increase in publications since 2016, accompanied by a paradigm shift from waste disposal toward resource recovery and circular economy approaches. This study proposes a quadruple system model consisting of institutional, operational, financial, and evaluative dimensions integrated with an educational dimension as a hidden curriculum. The proposed model is expected to support sustainable waste management and strengthen environmental education implementation in Adiwiyata schools.